High Lipase Production from Geotrichum candidum in Reduced Time using Cottonseed Oil: Optimization, Easy Purification and Specificity Characterization - Patrícia F. de Castro; Natália C. Moreira; Mateus N. Esperanca; Liliane M. de Oliveira; Alberto C. Badino; Olga L. Tavano; Adriano A. Mendes; Rodrigo C. Basso; Roberto Fernández-Lafuente; Daniela B. Hirata (Journal of Chemical Engineering Research Updates, 2017)
Despite the wide variety of potential applications of lipases within industrial processes, the high cost of production and purification is still their main limiting factor. The aim of this work is to optimize the production of Geotrichum candidum lipase (GCL) using submerged fermentation with a combination of statistical experimental design and surface methodology analysis, in order to give a higher production within a shorter time at the lowest possible cost and easy purification. Cottonseed oil, a low-cost by-product of cotton processing, was used as both an inducer and a carbon source. A maximum lipase activity of 27.17 IUmL-1 was achieved after 30h fermentation in a 5L stirred tank bioreactor under optimal conditions: 2.3% (m/v) of casein peptone, 0.8% (v/v) of cottonseed oil and 0.05% (m/v) of MgSO4 and NaNO3. The lipase purification in a single step by immobilization on PHB particles was verified. The combination of these two steps allowed a significant decrease in this lipase cost of production. Moreover, the produced lipase showed high specificity to hydrolyze long-chain fatty acids with cis-9 double bonds, such as oleic and linoleic acids, having an excellent potential for modifying oils in order to produce different bio-products in industrial applications.